Labor, land and agricultural credit policies and their adverse impacts on poverty in Brazil - Gervásio Castro de Rezende (Institute for Applied Economic Research (ipea), 2015)
This paper discusses the question of the concentrated pattern of agricultural development in Brazil, as expressed in the predominance of large-scale production, high level of mechanization and low absorption of non-qualified labor. It is proposed, initially, the existence of two conflicting explanations for this fact: the first, that blames our historical heritage, characterized by the predominance of the latifúndio, with the implication that the solution requires a radical agrarian reform; and the second, that sees in this concentrated pattern of agricultural growth in Brazil a technological determinism, with the implication that lesser concentration in agriculture would imply a loss in economic efficiency. Diverging radically from these two lines of arguments, this paper attributes to the agricultural labor and to the land policies that were instituted in the 1960s, and to the agricultural credit policy, instituted by the same time, the major responsibility for this problem. As argued in the paper, these policies turned unviable in Brazil not only the agricultural temporary labor market, but also family farm, at the same time that stimulated agricultural mechanization and the predominance of large-scale production. The paper ends up proposing, in a manner consistent with the analysis presented, that the only way to initiate the deconcentration of our agricultural growth would be through a radical de-regulation both of agricultural labor and land markets, instituting in Brazil, at last, free contracting, the most basic capitalistic institution.
Keywords: Q15; J43; J58; 330